The effect of peroxyacetic acid treatment at elevated temperature onto the Indonesian coal microstructure - Mohd Ishak, Mohd Azlan; Ismail, Khudzir; Ismail, Ahmad Faris (Faculty of Applied Science, Universiti Teknologi MARA, 2004)
A sub-bituminous high sulphur Indonesian coal, namely Banjarmasin Hj. Ali-Aliansar (BMHA) has been treated with peroxyacetic acid, a mild oxidising agent at temperature of 70°C and at atmospheric pressure. Initial findings have shown that this reagent is capable of removing up to 60 % of the total sulphur in the coal. Almost all pyrite together with ~18 % of simple organic sulphur are being removed from the coal without severely affecting the coal microstructures. Scanning electron microscope with energy dispersive x-ray (SEM-EDX) analysis was used to observe the molecular structure changes within the coal matrix.